Air and surface contamination in non-health care settings among 641 environmental specimens of 39 COVID-19 cases. - Lei Luo; Dan Liu; Hao Zhang; Zhihao Li; Ruonan Zhen; Xiru Zhang; Huaping Xie; Weiqi Song; Jie Liu; Qingmei Huang; Jingwen Liu; Xingfen Yang; et al. (Public Library of Science (PLoS), 2020)
Little is known about the SARS-CoV-2 contamination of environmental surfaces and air in non-health care settings among COVID-19 cases. We explored the SARS-CoV-2 contamination of environmental surfaces and air by collecting air and swabbing environmental surfaces among 39 COVID-19 cases in Guangzhou, China. The specimens were tested on RT-PCR. The information collected for COVID-19 cases included basic demographic, clinical severity, symptoms at onset, radiological testing, laboratory testing and hospital admission. A total of 641 environmental surfaces and air specimens were collected among 39 COVID-19 cases before disinfection. Among them, 20 specimens (20/641, 3.1%) were tested positive from 9 COVID-19 cases (9/39, 23.1%), with 5 (5/101, 5.0%) positive specimens from 3 asymptomatic cases, 5 (5/220, 2.3%) from 3 mild cases, and 10 (10/374, 2.7%) from 3 moderate cases. All positive specimens were collected within 3 days after diagnosis, and 10 (10/42, 23.8%) were found in toilet (5 on toilet bowl, 4 on sink/faucet/shower, 1 on floor drain), 4 (4/21, 19.0%) in anteroom (2 on water dispenser/cup/bottle, 1 on chair/table, 1 on TV remote), 1 (1/8, 12.5%) in kitchen (1 on dining-table), 1 (1/18, 5.6%) in bedroom (1 on bed/sheet pillow/bedside table), 1 (1/5, 20.0%) in car (1 on steering wheel/seat/handlebar) and 3 (3/20, 21.4%) on door knobs. Air specimens in room (0/10, 0.0%) and car (0/1, 0.0%) were all negative. SARS-CoV-2 was found on environmental surfaces especially in toilet, and may survive for several days. We provided evidence of potential for SARS-CoV-2 transmission through contamination of environmental surfaces.